Gigaseal Formation in Patch Clamping With Applications of Nanotechnology - Malboubi, Majid; Jiang, Kyle.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book presents an investigation of gigaseal formation using micro/nanotechnology. The aims of the book are twofold. First, it explains the mechanisms of gigaseal formation using the latest discoveries. Second, it provides practical techniques for frequent formation of high resistance seals. The formation of a high-resistance electrical seal, also known as a gigaseal, between a cell membrane and a glass micropipette tip is essential in patch-clamp experiments. Even though four decades have passed since the introduction of the patch-clamping technique by Neher and Sakmann, gigaseal formation remains an obstacle in developing the high-throughput ion channel screening systems required by the pharmaceutical industry. Here the authors share their latest methods for achieving gigaseal formation and describe techniques that are highly desirable at both research and industrial levels. Nanotechnology has been found to be a powerful tool for studying and modifying glass micropipettes and in tackling the problem of gigaseal formation.
Chapter 1 Introduction -- Chapter 2 Development of patch clamping -- Chapter 3 Gigaseal formation -- Chapter 4 Effect of roughness on gigaseal formation -- Chapter 5 Effect of hydrophilicIty on gigaseal formation -- Chapter 6 Effect of tip size on gigaseal formation -- Chapter 7 Study of glass micropipettes from tip formation to characterization -- References.
Keywords: Engineering; Biomedical engineering; Engineering; Nanotechnology and Microengineering; Biomedical Engineering